Pengembangan Desa Menuju Desa Wisata di Desa Timpag, Kabupaten Tabanan - Mahardika A.P., Ida Bagus; Gde Pujaastawa, Ida Bagus; Suwena, I Wayan (Humanis; Vol 25 No 2 (2021), 2021)
This research examines the development of the Tourism Village in Timpag Village, Tabanan Regency. The problem is focused on (a) the process and mechanism for the development of the Timpag Tourism Village, (b) the potential and constraints in the development of the Timpag Tourism Village, (c) The form of alternative solutions for developing potential and overcoming obstacles to the development of the Timpag Tourism Village. The problems were analyzed by using the Theory of Tourism Development and the Components of Tourism Attraction. This research uses qualitative methods including observation, interview, and document study techniques. The research resulted that the development of the Timpag Tourism Village was an initiative of a citizen which received positive responses from the community and the village government. The types of potential tourist attractions that are developed include natural, cultural, and artificial tourist attractions, development constraints include accessibility, facilities, infrastructure, marketing, insufficient institutions and human resources. Alternative solutions for development include structuring the potential for natural and artificial tourist attractions, while solutions to overcome obstacles include the development of accessibility, supporting facilities and infrastructure, promotion and marketing, as well as human resources and institutions.